Faktor Penentu Naik-Turunnya Harga Saham di Bursa Efek Indonesia - Agung Indradinata; Ida Bagus Raka Suardana; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe purpose of this study is to find out and analyze the effect of current ratio, debt to equity ratio, return on equity to dividend payout ratio and stock price. This study uses secondary data in the form of financial statements and stock price. The population in this study are all companies that had been registered in the LQ45 index during 2012 to 2017. By using the purposive sampling method, then obtained amount of sample counted 17 companies. The analysis technique used is path analysis. The results of this study indicate current ratio and debt to equity ratio have significant negative effect on dividend payout ratio. Return on equity have significant positive effect on dividend payout ratio and stock price, while the current ratio, debt to equity ratio and dividend payout ratio have no effect on stock prices. This study is expected to be a reference and material consideration of company management in managing the company and for investors in making investment decisions.